2014
DOI: 10.1590/1516-635x1604345-350
|View full text |Cite
|
Sign up to set email alerts
|

Corn replacement by broken rice in meat-type quail diets

Abstract: Alternative feedstuff, Coturnix coturnix, kani rice, rice by product.Submitted: September/2013 Approved: March/2014 ABStRACt An experiment was conducted to evaluate the effects of broken rice inclusion as substitute for corn in the diet on the performance, carcass yield, and economic viability of meat-type quails between 7 and 49 days of age. A number of 288 quails was distributed according to a completely randomized design into six treatments with six replicates of eight birds each. Treatments consisted of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 15 publications
6
4
0
1
Order By: Relevance
“…Similar to the present study regarding broken rice feeding, carcass, liver, breast, thigh, and drumstick yields did not differ significantly due to an increasing level of broken rice as a replacement for corn (19,25). In the case of DDGS feeding, our results are supported by findings in many studies (21,23).…”
Section: Discussionsupporting
confidence: 91%
“…Similar to the present study regarding broken rice feeding, carcass, liver, breast, thigh, and drumstick yields did not differ significantly due to an increasing level of broken rice as a replacement for corn (19,25). In the case of DDGS feeding, our results are supported by findings in many studies (21,23).…”
Section: Discussionsupporting
confidence: 91%
“…Under the conditions of our experiment, no significant difference was found in BW at 42, 56 and 70 d. No difference was observed in ADFI and ADG from 28 to 42 d. Similar results were reported in meat-type quails by Filgueira et al [25], who reported that meat-type quails fed with diets that replaced corn with BR did not differ in weight gain or feed intake from 7 to 49 d of age. These results indicated that replacing corn with BR in goose diets did not negatively affect BW (from 25% to 100%).…”
Section: Growth Performancesupporting
confidence: 91%
“…Results of the present work are in agreement with those of Filgueira et al (2014), who revealed that the replacement of corn by broken rice in the diets did not affect dressing percentage, breast, leg, liver, or gizzard yields of meat-type quails. According to Freitas et al (2006), when dietary nutritional levels are properly evaluated, it is unlikely that carcass yield is influenced by the inclusion of alternative feedstuffs in experimental diets in which most of the nutritional parameters are similarly in feed formulation.…”
Section: Resultssupporting
confidence: 92%
“…On the other hand, Edwin et al (2002) reported that feed consumption and feed efficiency did not show any significant variation among treatments contained different levels of broken rice. Also, Filgueira et al (2014) found that treatments consisted of increasing levels of broken rice (0, 20, 40, 60, 80 and 100%) in replacement of corn. Increasing levels of corn substitution by broken rice in the diet of 7-49 days old meat type quails did not affect feed intake, weight gain or feed conversion ratio (p>0.05).…”
Section: Resultsmentioning
confidence: 95%